Axial crushing of thin-walled structures with origami patterns - Song, Jie (2013)
Thin-walled tubes are a kind of popular design for the energy absorbing devices. However, when they are subjected to axial loading, there exists a large undesirable initial peak force, followed by fluctuation in the force–displacement curve. In this paper, the origami patterns are introduced to thin-walled tubes to minimize the initial peak and the subsequent fluctuations. Tubes of square, hexagonal and octagonal cross-sections with origami patterns are investigated by finite element analysis. Numerical results show that compared with the conventional tube, the patterned tubes exhibit a lower initial peak force and more uniform crushing load. The critical states are obtained under which the crushing mode follows the initial origami pattern. The parametric study shows the relationship between the pre-folding angle and the initial peak force as well as the mean crushing force for the tubes with different cross-sections. A prototype of the patterned tube is constructed and tested, showing much lower initial peak force and a smooth crushing process which agrees with the numerical results.